Trauma exposure and functional movement characteristics of male tactical athletes - Taylor, M. K.; Hernández, L. M.; Sessoms, P. H.; Kawamura, C.; Fraser, J. J. (Journal of Athletic Training, 2020)
Context: Tactical athletes commonly experience high levels of physical stress, which may increase their risk of musculoskeletal injury. It is critical to understand psychological predictors of functional movement (FM), which may help prevent musculoskeletal injury in this population. Objective: To determine the associations of combat and trauma exposure with FM characteristics of male tactical athletes. Secondary objectives were to explore confounding influences of age and physical injury history as well as the mediating role of bodily pain. Design: Cross-sectional study. Setting: Research laboratory. Patients or Other Participants: Eighty-two healthy, male, active-duty US Navy Explosive Ordnance Disposal personnel (age = 34.0 ± 6.7 years). Main Outcome Measure(s): Participants completed measures of combat exposure, trauma exposure, physical injury history, and bodily pain. We assessed FM characteristics (ie, Functional Movement Screen [FMS], Y-Balance Test), from which we derived a composite functional status (CFS) measure. Hypotheses were tested using correlational and multiple regression (causal-steps) models. Results: In unadjusted models, trauma exposure was inversely associated with the FMS (P = .005) and CFS (P = .009) scores. In adjusted models, these relationships were robust to the confounding influences of age and physical injury history. Trauma exposure and bodily pain were substantive, independent predictors of FMS and CFS in causal-steps models (all P values < .05), implying additive rather than mediated effects (R2adj = 0.18-0.20). Combat exposure did not predict FM characteristics. Conclusions: To our knowledge, this is the first evidence of the influence of trauma exposure on the FM characteristics of male tactical athletes, independent of age, physical injury, and bodily pain. This program of research may help to advance the prevention and treatment of musculoskeletal injuries in the tactical environment.